Orientación educativa para la mejora de la autoestima en estudiantes de primaria en la unidad educativa ciudad del norte - Loor Loor, Liliana Lilibeth (2025)
Self-esteem is a key factor in the comprehensive development of elementary school students at Ciudad del Norte Educational Unit, as it influences their emotional well-being, interpersonal relationships, academic performance, and coping abilities. Given the issue of low self-esteem in this context, the research posed the following question: How does educational guidance influence students' self-esteem? The general objective was to design and implement an intervention plan to strengthen self-esteem during the 2024-2025 school year. The study employed a mixed-methods approach (qualitative and quantitative), integrating data collection through the Self-Esteem Test (TAE-Students), surveys, interviews, and observation sheets. The results showed that 29.2% of students exhibited low self-esteem, facing challenges in social integration, perception of academic success, and emotional resilience. Expert evaluation validated the plan’s effectiveness, assigning an average score of 6/7 for strategy relevance and 7/7 for its expected impact on self-esteem. The study concluded that structured educational guidance based on psychopedagogical strategies can effectively strengthen students’ self-esteem, provided that key factors such as teacher training in early intervention, regular monitoring of indicators, and progressive plan implementation are included. Ongoing longitudinal follow-up and interdisciplinary collaboration are recommended to consolidate these improvements over the long term.